Phenotypic diversity within Ugandan yam (Dioscorea species) germplasm collection - Adjei, E.A.; Esuma, E.; Alicai, Titus; Bhattacharjee, Ranjana; Dramadri, I.; Agaba, R.; Chamba, E.; Odong, Thomas L. (Hindawi Limited, 2022)
A proper understanding of the diversity of the available germplasm is an initial step for the genetic improvement of a crop through breeding. However, there is limited information on the diversity of Uganda’s yam germplasm. The study sought to characterize the diversity of yam germplasm utilized for decades in Uganda together with germplasm recently introduced from West Africa using phenotypic traits. A germplasm collection of 291 genotypes was characterized using 28 phenotypic traits. Data were subjected to multivariate analysis using principal component analysis and cluster analysis. The traits assessed were informative and discriminating, with 62% of the total variation explained among the first six principal components. Results showed that the important phenotypic traits contributing to most of the variability among the genotypes were leaves, flowering, and tuber traits. Ugandan genotypes were identified with amorphous tuber shapes compared to West African genotypes. The study has shown that there is ample phenotypic variability within the major yam genotypes in Uganda yam germplasm that can be used for genetic improvement. More in-depth molecular and biochemical studies to further understand the diversity are recommended. The preprint was made available by research square in the following link: “https://www.researchsquare.com/article/rs-1518551/v1.”